Bistable N–H⋯N hydrogen bonds for reversibly modulating the dynamic motion in an organic co-crystal. Issue 16 (11th April 2016) - Ji, Chengmin; Li, Shenhui; Deng, Feng; Liu, Sijie; Asghar, Muhammad Adnan; Sun, Zhihua; Hong, Maochun; Luo, Junhua
Abstract : Bistable N–H⋯N hydrogen bonds enable the modulation of the dynamic molecular motion by slowing down the fast rotation in 1, 2-diazabicyclo(2.2.2)octane bis(thiourea). Abstract : Bistable N–H⋯N hydrogen bonds between rotors and stators enable delicate modulation of dynamic molecular motion by slowing down the fast rotation in a N–H⋯N hydrogen-bonded organic co-crystal of 1, 2-diazabicyclo(2.2.2)octane bis(thiourea), which has been elucidated by the combination of variable-temperature (VT) X-ray structure analyses and VT solid-state nuclear magnetic resonance techniques.